Comparison of arm, upper body and whole body double poling in female and male corss-country skiers - Hegge, A.; Bucher, E.; Ettema, G.; Sandbakk, O. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The double poling technique in cross-country skiing is a whole body movement where the arms, trunk and legs interact in producing power. When these body segments work together an increase in power output is expected compared to their isolated movements. Since previous findings show that gender differences increase with more contribution from poling, further examination regarding the different segmental contributions during double poling is required. Therefore, we examined the aerobic and anaerobic capacities and movement efficiency during isolated arm (AP), upper body (UP; arm+trunk) and whole body (WP) double poling and the associated gender effects. Methods: Ten female and ten male elite cross-country skiers, matched by performance (FIS points 99±26 and 99±21), performed three submaximal stages, a 3-min and a 30-s max test on a modified Concept2 SkiErg in the three double poling modes. The regression lines of oxygen uptake vs. external power during the submaximal stages determined efficiency, and the average power output during the 3-min and 30-s tests determined performance. Body composition was measured with DXA scan. Results: Women had a lower absolute oxygen uptake and produced less power than men (all P<0.05), but the oxygen uptake-power regression line did not differ between poling modes or gender. In the 3-min test UP power was more than 50% higher compared to AP, whereas WP was ~35% higher than UP (all P<0.05). The corresponding values for the 30-s test were ~40% from AP to UP, and 33 (women) and 18% (men) from UP to WP with a significant gender difference in the last case (all P<0.05). Women had a 51, 49 and 47% lower power output during the 3- min test and 53, 54 and 48% lower during the 30-s test compared to men in AP, UP and WP respectively, and these gender differences decreased to 22, 30, 29% (3-min) and 25, 37 and 30% (30-s) when normalized for the lean mass involved in each mode (all P<0.05). VO2peak in the 3-min test was ~32% higher for UP than AP, and 29 (women) and 18% (men) higher for WP than UP with a significant gender difference in the last case (all P<0.05). Discussion: The current study demonstrated large increases in power when the arms, trunk and legs work together compared to more isolated movements, with a particular importance placed on the role of the trunk in double poling. This finding also relates to the gender differences, indicating that the aerobic and anaerobic capacities of arms and trunk play crucial roles in explaining the gender gap in cross-country skiing. However, the ability to produce power for a given metabolic cost seems independent of exercise mode and gender. To extend upon these findings, the specific contributions from the upper and lower body joints in whole body double poling would be of high interest.